Era Otomatisasi: Dampak Terhadap Nilai Kemanusiaan, Etika, dan Risiko Dehumanisasi - Sriyani Mentari; Pramana, Andy Chandra; Agung Winarno (Fakultas Ekonomi Universitas Kadiri, 2025)
Automation technology has become a part of human life in this modern era. The wise development of automation technology needs to include consideration of human values, ethical values and mitigation of dehumanization risks. This study aims to identify the impact of automation technology on human values, ethical values and the risk of dehumanization using a systematic literature review method. Relevant journal articles published within the last 5 years were collected from Scopus, Web of Science and Google Scholar databases to be reviewed and analyzed. The results of the sistematic review show that automation technology has an impact on the erosion of empathy, freedom, transparency, dignity and justice. Automation technology also raises ethical issues such as violation of privacy and personal data, discrimination, safety risks and public trust. Finally, automation technology has the potential to cause dehumanization such as reduced interaction and replacement of human roles, depersonalization of services and objectification of humans.